Designing a learning trajectory for cube nets using the Engklek game: An educational design research study within realistic mathematics education - Eka Zuliana; Lalu Muhammad Fauzi; Femas Anggit Wahyu Nugroho (Jurnal Elemen, 2026)
The tendency to teach geometry mechanically highlights the need for mathematics instruction grounded in students’ daily contexts. This study designs a Learning Trajectory (LT) for cube nets using the engklek game—a traditional Indonesian hopping game—as a realistic context, framed within Realistic Mathematics Education (RME), and implemented through educational design research (validation study type). Conducted at one school in Kudus, the study involved 21 Grade 5 students across three phases: preparing for the experiment, designing the experiment (pilot and teaching experiment), and retrospective analysis. The resulting LT comprises four sequenced activities aligned with RME’s modeling levels—situational, model-of, model-for, and formal—through which students progressed from informal understandings (e.g., engklek kapal terbang as a cube net) to formal knowledge: recognizing eleven distinct cube nets organized into four pattern categories (1-4-1, 2-3-1, 2-2-2, and 3-3). This LT contributes to the expansion of instructional design in mathematics and provides teachers with a culturally responsive, game-based pedagogical tool that bridges students’ informal experiences with formal geometric concepts.